Feasibility and use of registry-based cancer survival analysis, demonstrated for malignancies of the colon, breast, prostate and bladder in Hamburg - Alice Nennecke (2007)
Population-based cancer survival analysis is an appropriate way of monitoring the effectiveness of prevention and treatment in the healthcare system. The Hamburg Cancer Registry (HCR) intends to apply this tool to improve the usability of its data stock. The objectives of this study are to assess the HCR’s database concerning survival analysis, to perform analyses within selected malignancies, and to evaluate the results in relation to the assessments of clinical specialists and external estimates. Four cancer sites and corresponding periods of diagnoses were chosen by the criteria minimum of 100 cases annually in Hamburg residents of each sex, ≥80% documented as having survived more than one day, and dominance of a histological type. Included were first primary malignancies of the colon, the prostate and the urinary bladder diagnosed in 1995-2003, as well as of the female breast diagnosed in 1992-2003. Cumulative observed and relative survival was estimated by site, sex, time, age and stage. In addition clinical oncologists from Hamburg were asked per post to estimate particular cancer survival trends since 1990, and to specify survival relevant developments of diagnostics and therapy by subject and time.